2020
DOI: 10.1177/1365480220934907
|View full text |Cite
|
Sign up to set email alerts
|

Socio-cultural factors influencing preschool enrolment in a rural cohort exposed to early parenting interventions in Pakistan: A qualitative study

Abstract: Early parenting interventions have shown to be effective for changing parenting behaviours to provide stimulation at home. However, evidence about the effect on decision to timely enrol the child in preschool and the related pathways is scarce. A follow-up study of a rural cohort exposed to early parenting interventions in the first 2 years of life in Pakistan though indicated benefits for children’s cognitive skills and learning environment at home but did not improve preschool enrolment rates. The aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Naushahro Feroze, predominantly a rural district has poor education indicators. High-quality preschool services specifically are almost non-existent [23]. In the original trial, the cohort of children was exposed to either Responsive Stimulation, Enhanced Nutrition, a combination of these, or standard care in the first two years of life starting from birth [20].…”
Section: Settingmentioning
confidence: 99%
“…Naushahro Feroze, predominantly a rural district has poor education indicators. High-quality preschool services specifically are almost non-existent [23]. In the original trial, the cohort of children was exposed to either Responsive Stimulation, Enhanced Nutrition, a combination of these, or standard care in the first two years of life starting from birth [20].…”
Section: Settingmentioning
confidence: 99%
“…However, some women are involved in handicraft. A qualitative study in the district revealed poor quality of education and preschool services especially in the public sector [30]. Challenges also included parental attitudes and lack of engagement with child's schooling and education.…”
Section: Settingmentioning
confidence: 99%